BENDUNG ARGOGURUH MASA KOLONISASI 1935-1942 - Febri Angga Saputra; Elis Setiawati (Swarnadwipa, 2021)
The problem in this study is the influence of irrigation in the Sukadana Colonization. The purpose of this study is to analyze and describe the implementation of ethical political policies in the irrigation sector in the Sukadana Colonization in 1935-1942. The research method uses historical methods with data collection techniques, in the form of primary and secondary sources. Based on the results of the study, that the implementation of ethical political policies in the irrigation sector coincided with the implementation of aspects of population transfer or migration, which was later known as colonization. In 1935 the construction of the Argoguruh Weir began. This weir serves to stem the Way Sekampung river which will then be channeled to the Sukadana Colonization farm. Besides being part of a trilogy of ethical politics. Irrigation was also very important for the survival of the colonists in Sukadana, the majority of whom were farmers. Irrigation development is one of the factors driving the success of colonization in Sukadana. This is evidenced by the abundant rice yields and the rapid population growth that made Metro the capital of the Sukadana colonization.